Highly Intensified Surface Enhanced Raman Scattering by Using Monolayer Graphene as the Nanospacer of Metal Film–Metal Nanoparticle Coupling System. (28th January 2014) - Li, Xuanhua; Choy, Wallace C. H.; Ren, Xingang; Zhang, Di; Lu, Haifei
<x xml:space="preserve">Abstract</x> It is widely accepted that surface enhanced Raman scattering (SERS) enhancement results from a combination of electromagnetic mechanisms (EM) and chemical mechanisms (CM). Recently, the nanoparticle‐film gap (NFG) system was studied due to its strong local enhancement field. However, there are still some technical limitations in establishing effective and simple ways for reliable and precise control of sub‐nanospacer. In addition, works on designing the nanospacer in NFG system for efficient interaction with target molecules for further improving SERS signals are rather limited. Here, a novel NFG system is proposed by introducing ultrathin monolayer graphene as well‐defined sub‐nanospacer between Ag NPs and Ag film (named G(graphene)‐NFG system). The new G–NFG system offers tremendous near‐field enhancement with one of the highest enhancement ratio of 1700 reported to date. These results show that the single‐layer graphene as a sub‐nanospacer renders the proposed G–NFG system with particularly strong EM enhancement (due to multiple couplings including the NP–NP couplings and NP‐film couplings) and additional CM enhancement in detecting some π‐conjugated molecules to function as a powerful tool in analytical science and the related fields.